Sustainable sucess in football: from clubs dynamic capabilities to sustained competitive advantage - Sismeiro, Francisco Quintela (2019)
In the last two decades, football has increasingly become a multimillionaire business, where clubs have started to be managed as companies, and consequently having the necessity to satisfy a great variety of stakeholders, not only on a financial level, but also considering their sporting performance. The increasing competitiveness, which led to an increase of clubs’ expenditures, along with a greater control regarding their finances, created the need to find different solutions in order to achieve a sustained competitive advantage. Although we recognize the importance of financial resources as a mean to achieve good sporting performances, this work focuses on its application on clubs’ dynamic capabilities, by maximizing the investment done, allowing to achieve good sporting performances, without putting at risk the clubs’ financial health. For this study, we considered the top 15 of highest earning clubs in the season 2016-17 and we analyzed their performance in that season and in the previous nine. Since season 2012-13, considering some indicators, we tried to establish some connections between good performance and the capabilities we considered essential in order to assure the clubs sustainability, such as an effective recruitment, the exploitation of youth academies and the capacity to generate higher revenues. Even though the explanatory power between sporting performance and some variables is not relevant, we were able to establish a pattern of common strategies that may be considered as crucial practices in order to achieve sustained competitive advantage.